Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jpeds.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Treatment of Depression, Anxiety, and Conduct Problems in US Children

Abstract: Objectives To use the latest data to estimate the prevalence and correlates of currently diagnosed depression, anxiety problems, and behavioral or conduct problems among children, and the receipt of related mental health treatment. Study design We analyzed data from the 2016 National Survey of Children's Health (NSCH) to report nationally representative prevalence estimates of each condition among children aged 3-17 years and receipt of treatment by a mental health professional. Parents/caregivers reported whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
508
10
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(594 citation statements)
references
References 34 publications
33
508
10
5
Order By: Relevance
“…Previous studies assessed the variation in the relation between body dissatisfaction and depressive symptoms by weight status or sex, but not both. The lack of significant differences in body dissatisfaction or depressive symptoms by sex in Black early adolescents is consistent with a study on body dissatisfaction among Black adolescents of~13 years [61], but contradictory to a study reporting a higher prevalence of depressive symptoms among females than males in a national representative sample of adolescents aged 12-17 years [62]. The finding that there was no significant moderating effect of sex for either weight group is contradictory to the two studies that found sex variation in the bidirectional relations between body dissatisfaction and depressive symptoms [30,31].…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies assessed the variation in the relation between body dissatisfaction and depressive symptoms by weight status or sex, but not both. The lack of significant differences in body dissatisfaction or depressive symptoms by sex in Black early adolescents is consistent with a study on body dissatisfaction among Black adolescents of~13 years [61], but contradictory to a study reporting a higher prevalence of depressive symptoms among females than males in a national representative sample of adolescents aged 12-17 years [62]. The finding that there was no significant moderating effect of sex for either weight group is contradictory to the two studies that found sex variation in the bidirectional relations between body dissatisfaction and depressive symptoms [30,31].…”
Section: Discussionsupporting
confidence: 72%
“…Although some studies have not confirmed the association between physical activity (PA) decline and changes in MH in adolescents, this does not undermine the importance of studying these associations [6]. e prevalence of mental disorders in 12-to 17-year-olds in the USA has been increasing [7,8], as is the case in Europe [9] and other countries [10]. In addition, while the prevalence of mental disorders is generally high, there exists significant inequality in MH among young people [11].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Psychiatric comorbidities are also common and are associated with adverse effects including greater disability and increased risk for persistence of headache into adulthood. 8,9 Given the high prevalence and the associated health consequences, headache in childhood may result in substantial economic costs to families, healthcare systems, and society. 7 Youth with headache are more likely to have at least 1 of these psychiatric comorbidities than the general population of youth in the United States, where prevalence estimates are 7.1% for anxiety disorders, 3.2% for depressive disorders, and 9.4% for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…7 Youth with headache are more likely to have at least 1 of these psychiatric comorbidities than the general population of youth in the United States, where prevalence estimates are 7.1% for anxiety disorders, 3.2% for depressive disorders, and 9.4% for ADHD. 8,9 Given the high prevalence and the associated health consequences, headache in childhood may result in substantial economic costs to families, healthcare systems, and society. Furthermore, the presence of psychiatric comorbidities may modify the effect of headache on healthcare expenditures by increasing disease burden and risk for high expenditures.…”
Section: Introductionmentioning
confidence: 99%